Binding energies of benzene on coinage metal surfaces: equal stability on different metals - Maaß, Friedrich; Tegeder, Petra (The journal of chemical physics, 2018)
Interfaces between organic molecules and inorganic solids adapt a prominent role in fundamental science, catalysis, molecular sensors, and molecular electronics. The molecular adsorption geometry, which is dictated by the strength of lateral and vertical interactions, determines the electronic structure of the molecule/substrate system. In this study, we investigate the binding properties of benzene on the noble metal surfaces Au(111), Ag(111), and Cu(111), respectively, using temperature-programmed desorption and first-principles calculations that account for non-locality of both electronic exchange and correlation effects. In the monolayer regime, we observed for all three systems a decrease of the binding energy with increasing coverage due to repulsive adsorbate/adsorbate interactions. Although the electronic properties of the noble metal surfaces are rather different, the binding strength of benzene on these surfaces is equal within the experimental error (accuracy of 0.05 eV), in excellent agreement with our calculations. This points toward the existence of a universal trend for the binding energy of aromatic molecules resulting from a subtle balance between Pauli repulsion and many-body van der Waals attraction.
Gesehen am 06.08.2019